PENGGUNAAN MEDIA BOARD GAME ULAR TANGGA DALAM PEMBELAJARAN IPAS SEKOLAH DASAR - Astiti, Niken Yuni; Rosyada, Balqis Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to describe the use of snake and ladder board game media in science learning in elementary schools. The sixth-grade students of SD Negeri 1 Metro Timur served as the research subjects. Data collection was conducted through observation, questionnaires, and documentation during the implementation of the learning media. The board game media used had been validated by media experts and material experts with a very valid category. The research results indicated that 86% of students were very active and 14% were active during learning using the snake and ladder board game media. Students' assessment of the use of the board game showed a positive response with an average score of 3.7 out of 4. The findings of this research indicated that the Snake and Ladders board game media created science learning that was interesting, interactive, and enjoyable for elementary school students.